2016
DOI: 10.2147/jir.s99887
|View full text |Cite
|
Sign up to set email alerts
|

TNF-related apoptosis-inducing ligand deficiency enhances survival in murine colon ascendens stent peritonitis

Abstract: BackgroundApart from inducing apoptosis in tumor cells, tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) influences inflammatory reactions. Murine colon ascendens stent peritonitis (CASP) represents a model of diffuse peritonitis. Recently, it has been demonstrated that administration of exogenous TRAIL not only induces apoptosis in neutrophils but also enhances survival in this model. The aim of this study was to examine the impact of genetic TRAIL deficiency on the course of CASP.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Moreover, the complex phenotypic syndromes, born by the identified and characterized 21 (KO MyD88-associated) target signaling pathways, contributed to the rapid progression of severe sepsis and even possible emerging death from complicated syndromes in post-operative mice, much beyond what has been perceived in literature ( 24 ). Our results update a significant advance in understanding the CASP-model sepsis mechanisms that have been explored for decades ( 4 , 8 , 24 , 27 , 31 , 52 56 ).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, the complex phenotypic syndromes, born by the identified and characterized 21 (KO MyD88-associated) target signaling pathways, contributed to the rapid progression of severe sepsis and even possible emerging death from complicated syndromes in post-operative mice, much beyond what has been perceived in literature ( 24 ). Our results update a significant advance in understanding the CASP-model sepsis mechanisms that have been explored for decades ( 4 , 8 , 24 , 27 , 31 , 52 56 ).…”
Section: Discussionsupporting
confidence: 64%
“…The pleiotropic effects of TRAIL on neutrophils and on T cells lead to conflicting results in peritonitis models and are a possible explanation for the sometimes seemingly contradictory results derived from infection models. Thus, TRAIL −/− mice display a survival advantage in a murine model of polymicrobial sepsis, an observation that is independent from neutrophils [79]. In concordance with these results, Gurung et al found that TRAIL −/− mice were better able to control a second-hit infection following peritonitis, suggesting that sepsis-induced immunosuppression was TRAIL-dependent.…”
Section: Trail and Its Interactions With T Cells: Lessons Learned mentioning
confidence: 80%
“…However, more recently it has been discovered that TRAIL also exerts a negative impact on immune cells [27, 29, 30] demonstrating promotion of tumour growth in a murine model of pancreatic cancer [31]. …”
Section: Discussionmentioning
confidence: 99%
“…TRAIL is a member of the TNF superfamily and was initially thought to selectively induce apoptosis in cancer cells [ 28 ]. However, more recently it has been discovered that TRAIL also exerts a negative impact on immune cells [ 27 , 29 , 30 ] demonstrating promotion of tumour growth in a murine model of pancreatic cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%